FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris Pada OPD-OPD di Kabupaten Kuantan Singingi) - Salami.JS Fajriana; Yusralaini Yusralaini; Hanif Afriana Rheny (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine and examine the factors that affect the Quality of Local Government Financial Reports. The factors tested in this study were the application of government accounting standards, human resource competencies, internal control systems, and work experience. The source of data used in this study is primary data and data collection is carried out directly using a questionnaire which is measured using a Likert scale. The population in this study were all OPD in Kuantan Singingi Regency, totaling 22 OPD. The total sample of this study was 110 respondents which consisted of the head of SKPD, secretary, head of the finance sub- section, revenue treasurer and expense treasurer with the sampling technique, namely purposive sampling. Reasons to use purposive sampling because the information to be taken is based on a source that is deliberately selected based on predetermined criteria. Data analysis using multiple linear regression which was processed with the help of SPSS version 25.00 program. The results of this study indicate that the application of government accounting standards, human resource competencies, and internal control systems have a significant effect on the quality of local government financial reports. While Work Experience does not significantly affect the Quality of Local Government Financial Reports.Keywords: Implementation of Government Accounting Standards, Human Resources Competene, Internal Control System, and Work Experience